Our organ donation experience in a braindead polycystic kidney disease patient: Case report - Hilmi Demirkıran; Celaleddin Soyalp; Mehmet Kilic; Cevdet Yardimci; Nureddin Yuzkat; Arzu Esen Tekeli; Muhammed Bilal Çeğin (Van Tıp Dergisi, 2018)
Polycystic kidney disease is an otosomal dominant hereditary disorder which can progress to end stage kidney failure. In this disease, the cysts in distinct sizes and distinct number are seen in kidneys and in liver. Nowadays, there is a great diffence in the number of donors and the patients waiting for transplantation. Because of that, using marginal donors may be necessary. In this article, we aimed to discuss whether a 55 years old braindead polycystic kidney disease patient can be used for transplantation or not.